Wound Healing Response to Full-Thickness Skin Defect Sprague Dawley Rats Given Ozonated Black Cumin Oil Viewing from The Profile of Neutrophil and Macrophage Count - Igor Rizkia Syahputra (Diponegoro International Medical Journal, 2022)
The incidence of wounds keeps increasing and inadequate treatment can cause the wound to become infected. Ozone has antibacterial properties and can help activate pro-inflammatory agents in the wound healing process; one of the methods is oil ozonation, for example with black cumin oil. Topical administration of black cumin plays a role in wound healing because of its antibacterial and antifungal properties, and plays a role in increasing the epitalization process. To determine the effectiveness of applying ozonated black cumin oil (Nigella sativa) on the healing process of full-thickness skin defects in Sprague Dawley rats, in terms of the number of macrophage and neutrophil cells. This research was an experimental study with a post-test only control group design method. Total sample of 48 Sprague Dawley rats was divided into 6 groups. The first group was given gentamicin ointment, the second group was given 0.9% normal saline, the third to the fifth group was given ozone black with doses of ozone respectively, namely 1400 mg/ml, 1800 mg/ml and 2200 mg/ml. Incision for taking the tissue samples was held on the 3rd and 7th day according to the treatment group. The tissue samples were subjected to histopathological examination with HE staining. A significant decrease in neutrophil levels occurred at the dose of 1,400mg/ml ozonated black cumin oil on day 7 (p=<0.001), dose of 1,800 mg/ml on day 3 (p=0.021) and day 7 (p=<0.001), doses of 2,200mg/ml at day 3 (p=0.020) and day 7 (p=<0.001) compared with a positive control group (given gentamicin). A significant decrease in macrophage levels occurred at a dose of 1,400mg/ml on day 3 (p=0.037) and 7 (p=0.019), a dose of 1,800 mg/ml on day 3 (p <0.001) and 7 (p=0.020), dose 2,200mg/ml on day 3 (p=<0.001) and day 7 (p=0.020).